KERAHIMAN ALLAH DI TENGAH KELUARGA KRISTIANI - Antonius Virdei Eresto Gaudiawan (Bahasa Indonesia, 2019)
Pope Francis promulgate Iubilaeum Extraordinarium Misericordiae. In the context of that jubilee, it is needed to reflect on the Christian family. How to make God’s Mercy radiat in the midst of Christian families through their problems. Christian families need God’s Mercy because nowadays, there are so much wounds exist in the families. We hope every Christian families receives God’s Mercy to encourage their lifes. Every people are called to show God’s Mercy in their own families. The research was made with qualitative research methods by reflecting the fundamentals of church faith such as the Scriptures and Church teachings. Furthermore, from the basis of this faith, the author will try to explore and reflect on the problem of the Christian family today. Next, look for and reflect on how God's merciful face is present in the midst of Christian families, now and here. Every family member needs to experience and realize. Forgiveness rooms are wide open for each family member. Grace rooms are open to every member of the Christian family who is involved.